2018
DOI: 10.3892/etm.2018.6297
|View full text |Cite|
|
Sign up to set email alerts
|

Fluvastatin inhibits cardiomyocyte apoptosis after myocardial infarction through Toll pathway

Abstract: The present study intended to investigate the effect of fluvastatin on cardiomyocyte apoptosis after myocardial infarction in rats. Eighty myocardial infarction rat models were established and randomly divided into 4 groups (n=20): experimental group (n=20) was given fluvastatin treatment; sham operation group (n=20) and normal control group (n=20) were given saline. The dose of fluvastatin was 20 mg/(kg·d), and irrigation gavage was given for 1 week. Western blot analysis and reverse transcription-quantitativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The pharmacological cardioprotective strategy to prevent acute global IRI has been tested using different approaches. Over the last few years, multiple pharmacological agents, including volatile anesthetic agents [55], [56], [57], sodium hydrogen exchange inhibitors [58] and statins [59], [60], [61], pharmacological preconditioning [62], [63], anti-oxidants [64], [65], anti-platelets [6], and anti-inflammatory strategies [66], [67], have been explored as potential cardioprotective therapies. However, most preclinical strategies showing cardioprotective effects did not work in clinical settings [68].…”
Section: Pharmacological Targets For Known Ischemia-reperfusion Injurmentioning
confidence: 99%
“…The pharmacological cardioprotective strategy to prevent acute global IRI has been tested using different approaches. Over the last few years, multiple pharmacological agents, including volatile anesthetic agents [55], [56], [57], sodium hydrogen exchange inhibitors [58] and statins [59], [60], [61], pharmacological preconditioning [62], [63], anti-oxidants [64], [65], anti-platelets [6], and anti-inflammatory strategies [66], [67], have been explored as potential cardioprotective therapies. However, most preclinical strategies showing cardioprotective effects did not work in clinical settings [68].…”
Section: Pharmacological Targets For Known Ischemia-reperfusion Injurmentioning
confidence: 99%
“…In recent years, a growing body of studies focusing on the regulatory mechanism of cardiomyocyte apoptosis confirms that apoptosis is of immense importance in MI progression. 15,16 It is widely accepted that the phosphoinositide 3-kinases (PI3K) pathway plays crucial roles in the regulation of cell survival. 17 Several investigations have identified that the PI3K pathway is implicated in myocardial apoptosis of heart diseases.…”
Section: Introductionmentioning
confidence: 99%